Evaluation of Hindrance to the Growth of SiN Passivation Layer by Contamination of Fluoride Ions in Front Opening Unified Pod (FOUP) - Song, Gil Joo; Hwang, Sung Min; Koo, Soo Jong; Kim, Hyoung Ryeun; Jang, Hee Chang; Hong, Jeong Hoon; Park, Hyun Yul; Choi, Euiji; Kim, Jin Young; Noh, Tae Yong; Lee, Eungsun; Yoo, Seoung-Kyo (TAIWAN ASSOC AEROSOL RES-TAAR, 2015)
We have investigated the hindrance to the deposition growth of silicon nitride (SiN) passivation layer from the contamination by airborne molecules in the front opening unified pod (FOUP). In particular, an artificial contamination of FOUP by fluoride ions as the source of the contaminants is utilized to elucidate the influence of contamination on the wafer surface. When the bare wafer surface is exposed to fluoride ions in the contaminated FOUP, the deposited thickness of the SiN layer is observed to decrease to a maximum of 11 angstrom from our experimental condition. On the other hand, there is no appreciable variation in the thickness of deposited SiN layer stored in the pre-cleaned FOUP. Based on the analytical results of wafer surfaces and FOUPs, we believe that the contamination of fluoride ions on wafer surfaces is originated from the contaminated surface of FOUP. Therefore, we conclude that it is necessary to clean and monitor the inside of FOUP on a regular basis, especially after wet or dry etching processes, which generates gaseous impurities.
Keywords: 300 MM WAFER; AIRBORNE MOLECULAR CONTAMINATION; NITROGEN